Humanister i offentlicheten: kunskapens aktörer och arenor under efterkrigstiden. - Östling, Johan, 1978- (Kriterium, 2022)
There is a strong story about how the humanities were marginalized in post-war Sweden: in the land of engineers, technocrats and social scientists, there was no room for education, philosophy and history. This book challenges such a notion and shows how clearly present the humanities were in the public eye at the time. By taking a knowledge-historical perspective, the authors illustrate how humanists were in the middle of the welfare society's culture and politics, media and book market, debate of ideas and education. At the center of the book is the public of the 1960s and 1970s. In the first part, it is highlighted how humanists played a decisive role in the young television's education program as well as in the popular science paperback publication of the time and on the essay pages of newspapers. In a second part, attention is drawn to the place of the humanities in the Christian cultural sphere, the work of educating the labor movement and the book cafes of the new left. We get to meet people like Per I. Gedin, Gunnel Vallquist and Jan-Öjvind Swahn, but also TV producers, study circle organizers, translators of radical non-fiction and several others. They all contributed to setting humanistic knowledge in motion during the post-war decades. Against an international background, the image of a humanistic knowledge system emerges with deep roots and wide branches in Swedish society. It is about these actors and arenas of knowledge that this book is about.